PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN CV. JAYA GEMILANG PAGAR ALAM - Sugeng Mianto Fane; Zubaidah Warni; Ahmad Brilian Alam (TECHNOBIZ : International Journal of Business, 2025)
The problem in this study is “do compensation and discipline have a partial and simultaneous effect on performance?” Hypothesis testing uses multiple linear regression analysis, through T-tests and F-tests, with the aim of determining the effect of independent variables on dependent variables at a 95% confidence level (a = 0.05). The results of the T-test on the compensation variable show a positive effect on performance, as seen from the t-value (5.403) > t table (2.042), significance (0.00) below or less than 0.05, while the work discipline variable has a positive effect on performance, as seen from the t count value (3.562) > t table (2.042) and significance (0.01) below or less than 0.05. In the F test, the variables and have a positive effect on performance, as seen from the F value (10.149) > F table (3.316), and significance (0.00) below or less than 0.05.